Full annual monitoring of Subantarctic Emiliania huxleyi populations reveals highly calcified morphotypes in high-CO2 winter conditions - Rigual-Hernandez, AS; Trull, TW; Flores, JA; Nodder, SD; Ruth Eriksen; Diana Davies; Gustaaf Hallegraeff; Sierro, FJ; Patil, SM; Cortina, A; Ballegeer, AM; Northcote, LC; et al. (2020)
Ocean acidification is expected to have detrimental consequences for the most abundant calcifying phytoplankton species Emiliania huxleyi . However, this assumption is mainly based on laboratory manipulations that are unable to reproduce the complexity of natural ecosystems. Here, E. huxleyi coccolith assemblages collected over a year by an autonomous water sampler and sediment traps in the Subantarctic Zone were analysed. The combination of taxonomic and morphometric analyses together with in situ measurements of surface-water properties allowed us to monitor, with unprecedented detail, the seasonal cycle of E. huxleyi at two Subantarctic stations. E. huxleyi subantarctic assemblages were composed of a mixture of, at least, four different morphotypes. Heavier morphotypes exhibited their maximum relative abundances during winter, coinciding with peak annual TCO 2 and nutrient concentrations, while lighter morphotypes dominated during summer, coinciding with lowest TCO 2 and nutrients levels. The similar seasonality observed in both time-series suggests that it may be a circumpolar feature of the Subantarctic zone. Our results challenge the view that ocean acidification will necessarily lead to a replacement of heavily-calcified coccolithophores by lightly-calcified ones in subpolar ecosystems, and emphasize the need to consider the cumulative effect of multiple stressors on the probable succession of morphotypes.